Power Relation in Catherine Steadman’s The Family Game - Christine P, Diva Niken Regina (State University of Makassar, 2026)
This study entitled Power Relations in Catherine Steadman’s The Family Game is focused on analyzing power relations that happen in the novel, mainly among the characters. This study uses Michael Foucault’s Power theory to find and examine power relationships, such as signs, causes, and effects of power relation among the main characters. This study uses extrinsic approach, that is a sociological approach. By using this approach, the study is conducted by analyzing power relations manifested in the novel. This study chooses the qualitative descriptive method, and the data source is the novel, The Family Game by Catherine Steadman. The data are collected by reading The Family Game thoroughly, collecting important parts such as words, phrases, and sentences to be used as evidence, finding journals and books to support the analysis, and organizing the evidence to arrange the analysis and connecting it with power relations. The findings show that the characters in the novel shows several signs of power, such as, authority, control, interest, gain, strategy, and communication. It is also finds that these power relations are influenced by status differences, personal goals, and family as a strong institution and cause resistance and knowledge. The results of the study indicate the power relations among each character and the shift of the dynamic, especially the main character, from powerless to the one who holds the most power in the novel. Through the characters, this study reveals how power can shape relationships, decisions, and the overall plot. Keywords: authority, control, power, power relation, strategy